Stem Cell Research: An Afro-Cultural Evaluation - Anifowose, Oluwaseun A. (Àgídìgbo: ABUAD Journal of the Humanities, 2019)
Stem cells are undifferentiated biological cells that can differentiate into specialized cells, divide to produce other cells and have been found useful in curative, preventiveand regenerative medicine. While some have argued for sustained researches using stem cells because of their curative and regenerative abilities, many others have countered-argued primarily because they believe the embryo is a potential source of life that should not be destroyed because of seemingly medical usefulness. This has generated controversies on the moral status of the embryo, the propriety of using cells obtained from embryos for research, the use of stem cells for therapeutic cloning, the place of human experimentation in African culture and the African view towards modern medical technologies. Moreover, is it just to destroy an embryo cell if it has the potential to cure many more people? Are human embryos means to an end? This paper argues that adult stem cells should be induced with pluripotent capacity and should be used as means of obtaining stem cells for research instead of embryonic stem cells because the use of adult stem cells is less controversial. This paper concludes that Africans should stop living in the shadows of the past and adjust to the current trends in the new global medical advances.